Cutaneous horn occurring on the oral tissues: report of a case and review of literature - Lucas C. Fallieri; Gabriela T. Ferreira; Beatriz M. C. Barbosa; Marcelo S. Araújo; Paulo Roberto Henrique; João Paulo S. Servato (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT The aim is to describe the clinical-pathological and treatment data of a patient with a cutaneous horn (CH) arising on oral tissues and to compare this with a literature-review. This case affects the lower-lip of an 86-years-old female. After excisional biopsy, the histopathological examination revealed a CH associated with actinic cheilitis. Only 23 similar cases have been reported in literature. At this site CH mainly affects the lower-lip of white males in a wide-age range. Excision should be the treatment of choice to enable pathological examination of the underlying lesion, since most cases were associated with pre-malignant/malignant lesions.